Characteristics of Ankylosing spondylitis patients in Kurdistan region of Iraq - Mahir Sadullah Saeed; Rasool, Mohammed Tahir (Asian Journal of Medical Sciences, 2022)
Background: Ankylosing spondylitis (AS) affects predominantly the axial skeleton and causes inflammatory low back pain. Aims and Objectives: We aimed to explore clinical characteristics of AS patients in Iraqi Kurdistan. Materials and Methods: In this cross-sectional study, the patients who attended a rheumatic disease center in Kurdistan Region of Iraq in 2022 were screened for the diagnosis of AS. Results: The mean age of the patients was 38.31 (17–65 years old) and most were Middle age and males (93.07%; male: female ratio: 13.43:1). The patients were normal sleepers (61.39%), short sleepers (28.71%), and long sleepers (9.90%). The patients were most physically active through walking. The age at symptoms onset of patients was 22.61 years (7–56 years). The patient’s disease was diagnosed at the mean value of 29.56 years. The median gap of diagnosis was 5 years. The patients had different characteristics; peripheral arthritis (56.44%), sacroiliitis (bilateral: 91.09%), tenosynovitis (14.85%), plantar fasciitis (45.54%), achilles tendinitis (17.82%), anterior uveitis (23.76%), positive human leukocyte antigen-B27 (88.40%), and spinal involvement (94.06%). Most patients received treatment (89.11%) including received biological treatment (53.47%) followed by multiple treatments (29.70%) and non-steroidal (4.95%) and only 0.99% (one patient) used physical therapy. The patients with normal sleepers and physically active and without extra-articular manifestations of AS had better disease severity and function compared to short sleepers and nonphysically active. Conclusion: A AS patients have escalating disease severity and function patients in this region. The disease severity and function were associated with healthy lifestyles such as sleeping and physical activity.